The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/02699052.2018.1483030
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in saccades and smooth-pursuit eye movements in adults with traumatic brain injury: a systematic review and meta-analysis

Abstract: TBI often results in long-standing OM deficits. Experimental measures of OM assessment reflect neural integrity and may provide a sensitive and objective biomarker to detect OM deficits following TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 66 publications
2
25
0
Order By: Relevance
“…Thus, antisaccade errors rather than latency appear to be a more sensitive marker of executive dysfunction. These findings are consistent with the results from studies conducted with adults with a history of concussion, which demonstrated that brain injury is associated with persistent errors on the antisaccade task even in cases when antisaccade latency is normal (Mani et al, 2018). The fact that stereopsis was correlated with inhibitory control in individuals with relatively good visual acuity suggests that stereoacuity may be a more sensitive test than acuity that could help to identify individuals with lower executive function.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, antisaccade errors rather than latency appear to be a more sensitive marker of executive dysfunction. These findings are consistent with the results from studies conducted with adults with a history of concussion, which demonstrated that brain injury is associated with persistent errors on the antisaccade task even in cases when antisaccade latency is normal (Mani et al, 2018). The fact that stereopsis was correlated with inhibitory control in individuals with relatively good visual acuity suggests that stereoacuity may be a more sensitive test than acuity that could help to identify individuals with lower executive function.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, the GMCT infers visual processing speed from the participants ability to follow a target using a computer mouse cursor. Measures of saccadic response are showing promise in being able to effectively distinguish between those with mTBI and those without [50]. Measures of saccadic reaction time involve attention and cognition [50] and incorporate diffuse networks across both cortical and subcortical structures [51].…”
Section: Discussionmentioning
confidence: 99%
“…Measures of saccadic response are showing promise in being able to effectively distinguish between those with mTBI and those without [50]. Measures of saccadic reaction time involve attention and cognition [50] and incorporate diffuse networks across both cortical and subcortical structures [51]. Assessments of saccadic reaction time may be more sensitive to subtle changes in a number of these pathways than more traditional cognitive assessments.…”
Section: Discussionmentioning
confidence: 99%
“…This accords with reviews and meta-analyses showing that mTBI minimally affects visually guided saccades but impairs saccades with more cognitive demands, namely antisaccades and memory-guided saccades. 54,55 In a related vein, a study using a simultaneous working memory task found that in mTBI saccades are only impaired under conditions of high cognitive load. 56 Despite these nuances, there is a suggestion that ocular motor deficits may be an objective biomarker of mTBI.…”
Section: Ocular Motor Dysfunction In Traumatic Brain Injurymentioning
confidence: 99%